Peyronie's Disease: Still a Surgical Disease. (26th August 2012) - Martinez, Daniel; Ercole, Cesar E.; Hakky, Tariq S.; Kramer, Andrew; Carrion, Rafael
Abstract : Peyronie's Disease (PD) remains a challenging and clinically significant morbid condition. Since its first description by François Gigot de la Peyronie, much of the treatment for PD remains nonstandardized. PD is characterized by the formation of fibrous plaques at the level of the tunica albuginea. Clinical manifestations include morphologic changes, such as curvatures and hourglass deformities. Here, we review the common surgical techniques for the management of patients with PD.